Evaluation of intrastromal voriconazole injection in recalcitrant deep fungal keratitis: case series. Issue 12 (31st March 2011) - Sharma, Namrata; Agarwal, Prakashchand; Sinha, Rajesh; Titiyal, Jeewan S; Velpandian, Thirumurthy; Vajpayee, Rasik B
Abstract : Aim: To evaluate the efficacy of intrastromal voriconazole, as a modality of treatment for management of recalcitrant fungal keratitis. Methods: Twelve patients of smear and/or culture positive fungal keratitis not responding to topical and systemic antifungal therapy were treated with additional intrastromal voriconazole therapy. Patients were given one or more intrastromal injection of voriconazole (50 μg in 0.1 ml) at the junction of clear cornea and infiltrates, using a 30-gauge needle in five quadrants to form a barrage around the ulcer. All patients continued to receive topical and systemic antifungal therapy. Results: The mean age of the patients was 47.58±15.13 years, and the mean time to presentation at the centre was 37.58±10.54 days. Organisms isolated were Aspergillus species (n=8), Fusarium species (n=3) and Curvularia (n=1). Of 12 eyes, 10 eyes healed with scar formation, and the mean resolution time was 39.75±7.62 days. Two corneas perforated and required therapeutic penetrating keratoplasty. The best-corrected visual acuity was less than 20/1200 in all patients at the time of presentation, which improved to better than 20/400 in 10 eyes and 20/40 in eyes that underwent penetrating keratoplasty at the end of 24.75±2.14 weeks' follow-up. Conclusion: Intrastromal injection of voriconazole may be used as a modality of treatment for managing cases of recalcitrant fungal keratitis.